The mindful way through depression freeing yourself from chronic unhappiness - Williams, J. Mark G; Teasdale, John; Segal, Zindel 1956-; Kabat-Zinn, Jon (New York, NY The Guilford Press, 2025)
"Description: The revolutionary book that has helped hundreds of thousands of readers find relief from chronic unhappiness is now in a revised and updated second edition. This authoritative, easy-touse self-help program is grounded in mindfulness-based cognitive therapy (MBCT), a clinically proven approach. The expert authors explain why our usual attempts to "fix" sadness or "talk ourselves out of it" can actually worsen recurrent depression instead of relieving it. Through vivid stories and downloadable audio meditations encouragingly narrated by Jon Kabat-Zinn, the book shows how to break the mental habits that lead to despair--and recover a sense of joy, aliveness, and possibility. Revised throughout to be even more reader friendly, the second edition features fresh insights on coping with the challenges of our ever-changing world; the latest scientific data; and four additional audio tracks. -- Keywords: mindfulness, meditations, audio tracks, body scan, downloads, files, mindfulness-based cognitive therapy, MBCT, self-help guide, psychology, mood disorders, personal development, exercises, practices, recovering from, preventing, sadness, despair, overcoming"--
"The revolutionary book that has helped hundreds of thousands of readers find relief from chronic unhappiness is now in a revised and updated second edition. This authoritative, easy-to-use self-help program is grounded in mindfulness-based cognitive therapy (MBCT), a clinically proven approach. The expert authors explain why our usual attempts to "fix" sadness or "talk ourselves out of it" can actually worsen recurrent depression instead of relieving it. Through vivid stories and downloadable audio meditations encouragingly narrated by Jon Kabat-Zinn, the book shows how to break the mental habits that lead to despair--and recover a sense of joy, aliveness, and possibility. Revised throughout to be even more reader friendly, the second edition features fresh insights on coping with the challenges of our ever-changing world; the latest scientific data; and four additional audio tracks"--
Includes bibliographical references and index.
Keywords: Attention; Depression, Mental; Happiness; PSYCHOLOGY / Psychopathology / Depression; SOCIAL SCIENCE / Social Work